2016
DOI: 10.4253/wjge.v8.i13.458
|View full text |Cite
|
Sign up to set email alerts
|

Electrocauteryvsnon-electrocautery dilation catheters in endoscopic ultrasonography-guided pancreatic fluid collection drainage

Abstract: EUS-TD using an electrocautery dilation catheter as a fistula dilation device for the treatment of symptomatic PFCs appears safe and contributes to a shorter procedure time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…In fact, one comparative study revealed that EUS-guided transluminal drainage of pancreatic fluid collections in the electrocautery group showed a significantly shorter procedure time than that in the nonelectrocautery group, although there was no significant difference in the technical success rates between both groups. [12] In contrast, several endosonographers who cannot use a coaxial 6Fr electro CD have used a conventional needle knife as a noncoaxial electrocautery dilator. However, it was reported that the use of a needle knife for fistula dilation was statistically significantly associated with postprocedure adverse events compared with graded dilation using non-CDs on EUS-BD.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, one comparative study revealed that EUS-guided transluminal drainage of pancreatic fluid collections in the electrocautery group showed a significantly shorter procedure time than that in the nonelectrocautery group, although there was no significant difference in the technical success rates between both groups. [12] In contrast, several endosonographers who cannot use a coaxial 6Fr electro CD have used a conventional needle knife as a noncoaxial electrocautery dilator. However, it was reported that the use of a needle knife for fistula dilation was statistically significantly associated with postprocedure adverse events compared with graded dilation using non-CDs on EUS-BD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a comparative study of mechanical dilation and coaxial electrocautery dilation in EUS-guided pancreatic fluid collection drainage showed no significant difference in the occurrence of adverse events. 19 Free air was seen as an immediate adverse event in only one case in the non-electrocautery group (1/28). Khashab et al also evaluated the adverse events in patients who underwent EUS-BD (n= 121).…”
Section: Technical Tips For Fistula Dilationmentioning
confidence: 95%
“…As mentioned above, a mechanical dilator is usually used first to dilate the puncture fistula [ 5 , 8 - 10 ]. Although cautery-assisted devices may prove to be more efficacious when pancreatic parenchyma is hardened from fibrosis [ 17 - 19 ], their use is limited and is often positioned as a subsequent method when dilation with mechanical devices fail. This is mainly because of the risk of adverse events associated with cautery devices.…”
Section: Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…This may not always be possible. Therefore, a fistula tract can be created using a cautery device, such as a needle-knife or cystotome (13,14). The tract can then be dilated with a 6 or 8 mm balloon dilator.…”
mentioning
confidence: 99%